Settling Down into a Long-Term Partnership : Successful Relationships for Sustainable Clients - Orton, Oliver; Heitmann, Soren (International Finance Corporation, Washington, DC, 2014)
After many years delivering corporate governance programs in Europe and Central Asia with in-house staff only, International Finance Corporation (IFC) moved to the next level with the objective of building local capacity to ensure the sustainability of corporate governance services in the market. But how should you set about selecting a partner for a long-term relationship? How do you manage the relationship over the life of the program? What if the relationship isn't working? Most important, how can you measure whether partner capacity is indeed improving? This smart lesson sets out some points to consider when engaging with a long-term partner in a capacity-building program, and some ideas on measuring whether capacity is being effectively built.